Energy demand and efficiency measures in polymer processing: comparison between temperate and Mediterranean operating plants - Khripko, D.; Schlüter, B.; Rommel, B.; Rosano, Michele; Hesselbach, J. (2016)
Polymer processing is an energy-intensive industry. The plastification of polymers requires a high volume of electric power for thermal energy. Electricity based power is the common form of energy in polymer processing and provides obvious potential for a reduction in energy use and costs. Measures to avoid production-based conversion losses, total conversion and transportation losses in energy used all have social, national, economic and business relevance. A bottom-up evaluation of four different production factories in this study assesses the potential for energy use improvements. The resulting theoretical assessment suggested that reducing primary energy demand is the most powerful target for reducing energy intensity in the polymer industry followed by the introduction of improved technologies to raise energy efficiency. The transferability of the conclusions was supported by the comparison between two different geographic locations for polymer production in Germany and Western Australia. The findings of this research suggest potential in their use in ‘green’ decision-making in the plastics industry.